Dynamic Unfolding and the Conventions of Procedure: Geometric Proportioning Strategies in Gothic Architectural Design. Issue 1 (20th June 2014) - Bork, Robert
Abstract : This essay explores the proportioning strategies used by Gothic architects. It argues that Gothic design practice involved conventions of procedure, governing the dynamic unfolding of successive geometrical steps. Because this procedure proves difficult to capture in words, and because it produces forms with a qualitatively different kind of architectural order than the more familiar conventions of classical design, which govern the proportions of the final building rather than the logic of the steps used in creating it, Gothic design practice has been widely misunderstood since the Renaissance. Although some authors in the nineteenth and twentieth centuries attempted to sympathetically explain Gothic geometry, much of this work has been dismissed as unreliable, especially in the influential work of Konrad Hecht. This essay seeks to put the study of Gothic proportion onto a new and firmer foundation, by using computer-aided design software to analyze the geometry of carefully measured buildings and original design drawings. Examples under consideration include the parish church towers of Ulm and Freiburg, and the cross sections of the cathedrals of Reims, Prague, and Clermont-Ferrand, and of the Cistercian church at Altenberg. The sequence of images being analysed can be viewed as supplementary material at: http://dx.doi.org/10.5334/ah.bq.s1